The implications of age-related neurofunctional compensatory mechanisms in executive function and language processing including the new Temporal Hypothesis for Compensation - Martins, Ruben; Joanette, Yves; Monchi, Oury (Frontiers in Human Neuroscience, 2015)
As the passage of time structurally alters one’s brain, cognition does not have to suffer the same faith, at least not to the same extent. Indeed, the existence of age-related compensatory mechanisms allow for some cognitive preservation. This paper attempts to coherently review the existing concepts of neurofunctional compensation when applied to two different cognitive domains, namely executive function and language processing. More precisely, we explore the Cognitive Reserve model in healthy aging as well as its two underlying mechanisms: neural reserve and neural compensation. Furthermore, we review the Compensation-Related Utilization of Neural Circuits Hypothesis as well as the Growing Of Life Differences Explains Normal Aging model. Finally, we propose, based on some functional neuroimaging studies, the existence of another compensatory mechanism characterised by age-related delayed cerebral activation allowing for cognitive performance to be preserved at the expense of speed processing: the Temporal Hypothesis for Compensation.